(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This scientific article discusses one of the most important issues for us: educating young people with high spirituality, modern knowledge and professional skills, and independent thinking in the spirit of national and universal values. Indeed, young people constitute more than half of our republic’s population. The article also addresses how youth understand the national idea, how it becomes their faith and conviction, and what new values are being formed. This is because, firstly, the national idea views youth as its object, and secondly, young people are considered the progressive developers of the national idea and its transmitters to future generations.